Analysis of Illocutionary Acts and Interrogative Meaning in the Hadith of Arba'in Nawawi: A Balaghah Study - Aji Rizqi Ramadhan -; Hairuddin Arsyad; Maman Abdurrahman; Miqdad Abdul (Arabiyyatī: Journal of Arabic Language Education, 2024)
Abstract This research examines illocutionary speech acts and interrogative meaning in the Hadith of Arba'in Nawawi from the perspective of balaghah science. The aim is to understand the meaning and message of the Prophet Muhammad SAW through interrogative sentences (istifham) in the hadith. This research uses a qualitative descriptive approach by analyzing 42 Arba'in Nawawi hadiths data. The results of the research show that there are ten istifham sentences in 6 hadiths which contain istifham sentences which have the following meanings: tasywiq (Encouragement), istib'ad (improbability), amr (command), inkar (denial), taqrir (affirmation), ta 'ajjub (Astonishment), and nafy (negation). The illocutionary speech acts found include assertive (declaring, claiming, confirming), directive (arousing curiosity, directing, ordering, warning, asking for attention), and expressive (expressing disbelief and admiration). This research contributes to understanding the meaning of the Prophet Muhammad SAW through the approach to the meaning of istifham and illocutionary speech acts and admiring the rhetoric and choice of words used by the Prophet Muhammad SAW in conveying the guidance of the Islamic religion.Keywords: Illocutionary Act, Interrogative Meaning, Arba'in Nawawi, Balaghah.